PROSPECTIVE EVALUATION OF A 5 × 4 Gy PRESCRIPTION FOR PALLIATION OF CANINE NASAL TUMORS. Issue 1 (24th September 2012) - Tan‐Coleman, Birgitte; Lyons, Jarred; Lewis, Craig; Rosenberg, Mona; Ruiz, Azucena
<x xml:space="preserve">Abstract</x> We evaluated the efficacy of palliative radiation therapy using 5 × 4 Gy given daily in 18 dogs with nasal tumors. Dogs with malignant nasal tumors were evaluated for response rate, response duration, and survival. Seventy‐eight percent of the dogs achieved complete resolution of clinical signs, and 16.5% had partial resolution of their signs. Overall median response duration for all dogs was 178 days after one course of radiation therapy. Six dogs received a second course of therapy when their disease progressed using the same daily 5 × 4 Gy scheme, and all six responded for a median time of 129.5 days for an overall median survival time in these six dogs of 309 days. Based on these results, a radiation prescription of 5 × 4 Gy appears to be useful palliatively in dogs with a malignant nasal tumor.